2010
DOI: 10.1590/s2176-94512010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Padronização de um método para mensuração das tábuas ósseas vestibular e lingual dos maxilares na Tomografia Computadorizada de Feixe Cônico (Cone Beam)

Abstract: INTRODUÇÃO: a espessura das tábuas ósseas que recobrem os dentes por vestibular e lingual constitui um dos fatores limitantes da movimentação dentária. O avanço tecnológico em Imaginologia permitiu avaliar detalhadamente essas regiões anatômicas por meio da utilização da tomografia computadorizada de feixe cônico (TCFC). OBJETIVO: descrever e padronizar, pormenorizadamente, um método para mensuração das tábuas ósseas vestibular e lingual dos maxilares nas imagens de tomografia computadorizada de feixe cônico. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
6
1
2
Order By: Relevance
“…31 Contrary to the findings of Ferreira et al, 31 greater dehiscence prevalence was observed in the present study at the cervical level in hyper-divergent samples. In hyper-divergent patients, the direction of condylar growth is mainly in the posterior direction and teeth are positioned inclined.…”
Section: Discussioncontrasting
confidence: 99%
“…31 Contrary to the findings of Ferreira et al, 31 greater dehiscence prevalence was observed in the present study at the cervical level in hyper-divergent samples. In hyper-divergent patients, the direction of condylar growth is mainly in the posterior direction and teeth are positioned inclined.…”
Section: Discussioncontrasting
confidence: 99%
“… 13 Additionally, buccal and lingual ABT at the cervical and middle thirds of the root was similar for both hyperdivergent and hypodivergent vertical facial patterns. 14 Similarly, both buccal and lingual ABT at the middle root third demonstrated a weak correlation with vertical facial patterns. 15 Importantly, thin anterior alveolus could be found in any skeletal types.…”
Section: Introductionmentioning
confidence: 97%
“…Thickness of the bone plate on the cervical and medium thirds of the root is very similar in the different facial types (FERREIRA et al, 2010), but the distance from the apex to the outer surface of the 1597 The influence of fränkel-2… VASCONCELOS, A. C. et al…”
Section: Discussionmentioning
confidence: 99%